284 Cognitive Deficits due to Insufficient Sleep are Mitigated Following Strenuous Physical Exertion in Firefighters. (3rd May 2021) - Stepan, Michelle; Wilckens, Kristine; Hostler, Dave; Franzen, Peter
Abstract: Introduction: Insufficient sleep impairs cognitive function which results in costly errors. Firefighter shifts regularly exceed 24-hrs with little to no sleep. Nevertheless, firefighters must maintain and flexibly shift attention in high-pressure scenarios. Firefighters also engage in strenuous physical exertion during fire suppression activities. However, it is unclear whether physical exertion acts as another stressor, exasperating cognitive deficits due to insufficient sleep, or whether physical exertion enhances arousal to reduce cognitive deficits. Moreover, the effects of physical exertion may depend on the type of cognitive process and extent of sleep loss. We examined the effect of physical exertion on vigilant attention and task-switching in firefighters who underwent sleep-deprivation or sleep-disruption. Methods: Participants were 17 healthy young adult males who participated in a within-subjects crossover design with three experimental lab visits: sleep-deprivation, sleep-disruption (woken 3 times for 60-min each), and normal sleep. The next day, participants completed a 50-min treadmill exercise task in a heated room in firefighter protective clothing. Participants completed a vigilant attention task (Psychomotor Vigilance Task, PVT) and a task-switching task five to nine times each visit. The five timepoints of interest–before and after the sleep manipulation night, before and after the treadmill exercise task, and recovery (approximately 180-min following exercise)–were examined using linear mixed effects models. Results: We analyzed lapses (reaction times [RT]>500ms) on the PVT and switch-trial RT and accuracy on the task-switching task for sleep-deprivation and sleep-disruption conditions relative to normal sleep. Sleep-disruption, p=.001, and sleep-deprivation, p<.001, increased lapses. Sleep-disruption increased switch-trial RT, p=.01, and sleep-deprivation reduced switch-trial accuracy, p=.01. Only switch-trial accuracy improved immediately after the treadmill exercise task and only for the sleep-deprivation condition, p=.01. During recovery, lapses lessened for the sleep-deprivation condition, p=.049, and switch-trial accuracy improved for both sleep-deprivation, p=.01, and sleep-disruption conditions, p=.049. Conclusion: Physical exertion reduced task-switching and attentional deficits caused by insufficient sleep, with more benefits observed during recovery. We found no evidence for performance decrements due to physical exertion. Physical exertion may interact with the extent of sleep loss–primarily benefitting performance under conditions of total sleep-deprivation. Support (if any): DSF Charitable Foundation and University of Pittsburgh Clinical and Translational Science Institute UL1TR001857.